2016
DOI: 10.1055/s-0042-111521
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Puerarin against Aβ 1–42-Induced Learning and Memory Impairments in Mice

Abstract: Puerarin is a major isoflavone glycoside from the root of It has been reported that puerarin can protect neurons from oxidative stress-induced apoptosis. Emerging evidence suggests that oxidative damage is associated with A-induced neuronal death. In the current study, we evaluated the effect of puerarin on Alzheimer's disease induced by A and explored the potential mechanisms underlying this effect. We found that the escape latency of the Morris water maze was decreased in groups treated with puerarin compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Pathological conditions of AD are evidenced to link with oxidative stress, and the level of lipid peroxidation is considered as an important factor in AD (Gao et al ., 2012). The level of MDA, a marker of lipid peroxidation index, was evaluated in hippocampus rather than cortex since a high level of MDA is induced in hippocampus after ICV injection of Aβ 1–42 (Ziech et al ., 2010; Wu et al ., 2017). Our results showed that spinosin significantly attenuated the up-regulation of MDA in hippocampus induced by ICV injection of Aβ 1–42 .…”
Section: Discussionmentioning
confidence: 99%
“…Pathological conditions of AD are evidenced to link with oxidative stress, and the level of lipid peroxidation is considered as an important factor in AD (Gao et al ., 2012). The level of MDA, a marker of lipid peroxidation index, was evaluated in hippocampus rather than cortex since a high level of MDA is induced in hippocampus after ICV injection of Aβ 1–42 (Ziech et al ., 2010; Wu et al ., 2017). Our results showed that spinosin significantly attenuated the up-regulation of MDA in hippocampus induced by ICV injection of Aβ 1–42 .…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the treatments were administered with Epimedium, Astragaoside and Puerarin, which are composed of active compounds, icariin, astragalosideIV and puerarin, respectively. Many studies have confirmed the uses of these active compounds in the treatment of neurological disorders [13, 18, 25]. Several studies have reported that these compounds may antagonize Aβ formation, scavenge free radicals, reduce inflammation, regulate mitochondrial functions and promote axonal maturation in the central nervous system [13, 18, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed the uses of these active compounds in the treatment of neurological disorders [13, 18, 25]. Several studies have reported that these compounds may antagonize Aβ formation, scavenge free radicals, reduce inflammation, regulate mitochondrial functions and promote axonal maturation in the central nervous system [13, 18, 26, 27]. Icariin, a component extracted from Epimedium, has a beneficiary action on experimental spinal cord injury through its anti-oxidant, anti-neuroinflammatory, and anti-apoptotic role [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also shown the neuroprotective effects of 23 in AD [ 214 , 215 ]. Puerarin also suppresses the A β (1–42) -induced primary cortical neuron death [ 216 ] thus protecting against A β (1–42) -induced learning and memory impairments in mice [ 217 ]. It also attenuates myocardial hypoxia/reoxygenation injury by inhibiting autophagy via the Akt signaling pathway and inhibits oxidative stress in STZ-induced SAD mice [ 218 , 219 ].…”
Section: Classical Examples Of Neuroprotective Drugs Of Plant-origmentioning
confidence: 99%